Factors Associated with Febrile Treatment-seeking Behaviour among Expectant Mothers in Ssekanyonyi, Mityana District, Uganda - Nanjobe Uniah; David R. Mutekanga; Christopher Ddamulira; Stephen S. Kizza; Lawlence Sserwanga (Disease and Health Research - New Insights Vol. 1, 2024)
Background: Febrile disease is very common among pregnant women in developing countries and sometimes not given relevant due diligence and perceived as a minor or common malaria situation. However, febrile disease most times is accompanied with some major disease condition which is life threatening to the pregnant women. This is a serious health problem that contributes greatly to morbidity and mortality in most developing economies including Uganda. In Mityana District of Uganda, 4 in 10 pregnancy deaths are malaria related and mothers who do not seek treatment in health facilities when they experience febrile illnesses. This is a major health challenge. Aim: The present study was undertaken to identify factors associated with treatment-seeking behavior among pregnant women suffering from febrile illnesses suspected to be malaria in Ssekanyonyi Sub-County in Mityana District, Uganda. Methods: A cross-sectional study in which questionnaires were administered to 198 expectant mothers to generate data on their socio-demographics and treatment seeking behaviour. SPSS software version 20.0 was used for data analysis and a Logistic Regression model was fitted to identify factors that independently influenced their treatment-seeking behavior. Relevant REC authorization and standard operating procedures of the Uganda Ministry of Health were duly followed. Results: Out of the198 expectant mothers enrolled in the study, 42.9% were aged 15-25 years, 73.7% had achieved Secondary education, and 46.5% were married. The treatment-seeking behavior was found to be standing at only 56.6%. Among the different factors studied, health education on malaria (AOR = 3.68, P = 0.000), the attitude of midwives (AOR = 1.45, P = 0.003), patient care (AOR = 0.33, P = 0.030), and attitude of the pregnant mother (AOR = 5.38, P = 0.000) were found to be statistically significantly associated with treatment-seeking behavior among pregnant mothers with febrile illnesses. The results show that the attitude of midwives is significantly associated with treatment-seeking behavior for febrile illnesses assumed to be malaria among pregnant mothers. Conclusion: The study concluded that health education and awareness on malaria, attitude of midwives and pregnant mothers, and how the pregnant mothers are handled are the most important factors in positively affecting treatment seeking behavior among pregnant mothers with febrile illnesses. Recommendations: Health education on malaria, midwives’ attitudes, patient treatment, and pregnant mothers’ attitudes must all be addressed in order to prevent febrile infections. The Ministry of Health and other responsible stakeholders must reinforce health education programs for women of reproductive age about the dangers of febrile illnesses during pregnancy. It is also critical to assist midwives in addressing issues related to their attitudes toward pregnant mothers.